2007
DOI: 10.1038/sj.gt.3303060
|View full text |Cite
|
Sign up to set email alerts
|

Viral vector-based prime-boost immunization regimens: a possible involvement of T-cell competition

Abstract: Vaccination with recombinant viral vectors may be impeded by preexisting vector-specific immunity or by vector-specific immunity induced during the priming immunization. It is assumed that virus-neutralizing antibodies represent the principal effector mechanism of vector-specific immunity, while killing of infected cells by vector-specific cytotoxic T lymphocytes (CTLs) has also been suggested. Using recombinant Semliki Forest virus (rSFV) expressing E6E7 antigen from human papillomavirus, we demonstrate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 47 publications
5
15
0
Order By: Relevance
“…More importantly, this CD8 T-cell response which decreased after the peak on day 7 after initial priming was boosted with a second immunization without de novo synthesis of antigen. Similar results were reported by de Mare et al [31]. Using recombinant Semliki Forest virus (rSFV) expressing E6E7 antigen from human papillomavirus, they demonstrated that secondary immune responses against E6E7 are neither affected by vector-specific antibodies nor by CTL-mediated killing of infected cells.…”
Section: Discussionsupporting
confidence: 84%
“…More importantly, this CD8 T-cell response which decreased after the peak on day 7 after initial priming was boosted with a second immunization without de novo synthesis of antigen. Similar results were reported by de Mare et al [31]. Using recombinant Semliki Forest virus (rSFV) expressing E6E7 antigen from human papillomavirus, they demonstrated that secondary immune responses against E6E7 are neither affected by vector-specific antibodies nor by CTL-mediated killing of infected cells.…”
Section: Discussionsupporting
confidence: 84%
“…Preclinical and clinical trials of combinations of various modalities (DNA vaccines, viral vectors, bacterial vectors, recombinant proteins) have been performed (Nabel et al, 2010), with the most extensive being the 16,000 patient trial for an HIV vaccine described above, consisting of a pox vector followed by a recombinant protein boost (RerksNgarm et al, 2009 The immunologic explanation for the increased immune responses in prime boost protocols and the reason that the sequence of priming with DNA plasmid followed by another modality, whether recombinant protein or viral vector, is necessary are not well understood. However, the lack of additional viral antigens (of the vector) when DNA is the prime, may help focus the immune response on the key antigen (de Mare et al, 2008). The additional innate antiviral responses, and cytokine milieu that develop following the viral vector boost, may augment the booster response.…”
Section: Prime-boost Immunizationmentioning
confidence: 96%
“…If a recombinant virus was used to prime as well as boost, the effect may not be quite the same, as the immune responses generated by the prime would be primarily an inflammatory response that, when boosted with the same vector, would result in a rapid decline of the vaccine vector [64]. Some of these effects are brought about by the presence of vector specific antibodies formed during the priming response but there is evidence to suggest that T cell-mediated mechanisms may also play a significant role [65]. Some researchers, however, have reported success using multiple immunizations with viral vector based vaccines [66,67] but this approach has not been adopted in veterinary vaccine development.…”
Section: Adenoviral Vector Based Vaccines In Prime Boost Protocolsmentioning
confidence: 99%